Acoustical Behaviour of Sodium Nitroprusside in Aquo-Organic Solvent Media at 308.15 K - Monalisa Das; Smrutiprava Das; A. K. Pattanaik (Journal of Chemistry)
Density and ultrasonic velocity have been measured for sodium nitroprusside in aqueous solutions of CH3OH, ethylene glycol, DMSO, and n-propanol solvents at 308.15 K. A quantitative relationship has been established among the acoustical properties like ultrasonic velocity (U), adiabatic compressibility (β), intermolecular free length (Lf), acoustic impedance (Z), apparent molar compressibility (Kϕ), apparent molar volume (Vϕ), limiting apparent molar compressibility (Kϕ0) limiting apparent molar volume (Vϕ0), and their constants (SK, Sv). From the obtained values, molecular interaction study has been made successfully in the light of these acoustical properties through hydrogen bonding in solute and solvent mixture.